Covariation between Childhood-Trauma Related Resting-State Functional Connectivity and Affective Temperaments is Impaired in Individuals with Major Depressive Disorder. (15th January 2021) - Wu, Huawang; Wu, Chao; Wu, Fengchun; Zhan, Qianqian; Peng, Hongjun; Wang, Jiaojian; Zhao, Jingping; Ning, Yuping; Zheng, Yingjun; She, Shenglin
Highlights: A profile of intrinsic FCs is associated with affective temperaments (AT). The FC-AT covariation is enhanced in patients with MDD. The AT-modulated FCs contributes to somatization depression. Abstract: Affective temperaments and childhood-trauma experiences are associated with major depressive disorder (MDD). So far, how the covariation between distinct affective temperaments and childhood-trauma insulted brain functional connectivities (FCs) contribute to MDD remains unclear. Here, we aimed to investigate whether certain brain FC patterns are related to certain affective temperaments and whether the FCs contribute to depressive symptom dimensions of MDD patients. Twenty-nine medication-free MDD patients and 58 healthy controls underwent magnetic resonance imaging scanning and completed the Hamilton Depression Rating Scale (HDRS), the Hamilton Anxiety Rating Scale (HARS), the Childhood Trauma Questionnaire-Short Form (CTQ-SF), and the Temperament Evaluation of Memphis, Pisa, Paris and San Diego (TEMPS). Two multivariate analyses of partial least squares (PLS) regression were used to explore the associations among childhood-trauma related resting-state FCs, affective temperaments and depressive symptom dimensions. In all participants, a linear combination of 81 FCs (involving parahippocampus, amygdala, cingulate cortex, insula, frontal–temporal–parietal–occipital cortex, pallidum, and cerebellum) were associated with a linear combination of increased depressive, irritable, anxious, and cyclothymic temperaments. Moreover, the covariation between the PLS FC profile and the PLS affective-temperament profile were enhanced in the MDD patients compared to healthy controls. In MDD participants alone, the affective-temperament modulated FC profile (mainly of the lingual and temporal cortex) was associated with the somatization symptom dimension when age, sex, ill-duration, age-of-onset, and HARS scores were adjusted. The findings imply possible neural correlates of affective temperaments and may find applications in intervention of the somatization-depression symptoms by stimulation of the related neural correlates.